A case study of instructors’ cultivation of creative thinking in an adult learning environment - Brown, Patricia Anne (Kansas State University, 2022)
The world is changing at a frenetic pace. Current creativity research and literature reveals how important it is for adults to live and work in environments conducive to creative learning and thinking. In education, we know that instructors influence the learning environment significantly, but we do not have a clear understanding of how instructors cultivate a climate for creative learning and thinking for adult learners. The purpose of this research was to understand how instructors cultivate a climate for creative learning and thinking for adult learners. This qualitative case study explored the experiences of a small group of instructors qualified to teach the Red Team Member Course, a unique four-week course that is part of the Red Teaming Education Program conducted by the Department of the Army. Three instructors volunteered from this group using convenient sampling. Four semi-structured interviews and three classroom observations were conducted with each instructor. Data from interviews, observations, course documents, and instructor artifacts were analyzed for emerging concepts, patterns, and themes using the theoretical framework of the investment theory of creativity. Results emerging from the findings confirm evidence of the six creativity constructs of the investment theory of creativity exists in the learning environments of the Red Team Member Course instructors. The convergence of the six creativity constructs, personality, motivation, knowledge, intellectual abilities, environment, and thinking skills, provides evidence of how instructors cultivate a climate for creative learning and thinking for adult learners in this unique learning environment. These findings have implications for professional development and training for adult educators and the learning experiences for adult learners.
Keywords: Creative learning environment; Creativity and adult learners; Creativity and adult educators; Creativity and military education; Creativity and adult education; Creativity